„Poślubię kardynała…” – małżeństwo Armanda księcia Conti i Anny Marii Martinozzi - Skrzypietz, Aleksandra (Studia Europaea Gnesnensia, 2015)
Armand de Bourbon, Prince of Conti, was a younger brother of the Grand Condé. Destined for a church career, he gave it up and became politically associated with brother and sister – the famed intriguer Anna Genevieve, Duchess of Longue¬ville. Desiring to be regarded as a person unconstrained by moral principles, he led a very indulgent lifestyle. For a period of time, he was also Moliere’s patron. Armand wanted to equal his brother in renown, though he lacked the talent. For some time, he was considered the leader of the Fronde in Paris. He was imprisoned together with his brother and brother-in-law, then sought agreement with the court. His influences were to be boosted by marriage, first with the daughter of duchess de Chevreuse, then with the niece of Cardinal Mazarin – Anna Maria Martinozzi, which indeed took place. The marriage of a relative with a prince of the blood strengthened the position of the cardinal, while prince of Conti gained a way for final conciliation with the court. In the later years, Armand was a commander in Spain and held various court offices; he also changed his lifestyle utterly, having associated himself with the Jansenists. Armand died young, leaving two sons, the younger of which became a candidate for the Polish throne in 1697. His biography, in particular the issues relating to the marriage, are an interesting example of court intrigues and a game whose purpose was to consolidate the position of both Cardinal Mazarin and the royal cousin. The conduct of prince of Conti is also a vivid example of the mores of aristocracy in 17th-century France.